2019
DOI: 10.33594/000000173
|View full text |Cite
|
Sign up to set email alerts
|

Uremia and Hypoxia Independently Induce Eryptosis and Erythrocyte Redox Imbalance

Abstract: Background/Aims: Red blood cell (RBC) death could contribute to anemia in chronic kidney disease (CKD) patients. Recent observational research has suggested a relationship between RBC death (eryptosis) and hypoxemia in hemodialysis patients. Thus, we studied the isolated and joint effects of a uremic toxin (indoxyl sulfate; IS) and hypoxia on RBC biology. Methods: We incubated RBC from healthy donors with IS at concentrations of 0.01mM, 0.09mM and 0.17mM under both normoxic (21% O 2 ) and hypoxic (5% O 2 ) con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…24 We have shown that hypoxia and IS promote eryptosis and alter the RBC redox system, increasing ROS formation and decreasing GSH content. 9 Here, we highlight the role of hypoxia in establishing oxidative stress and show for the first time that uremic serum potentiates these effects. This finding is particularly interesting for HD patients since arterial O 2 saturation can drop below 90% for more than 1/3 of treatment time in about 10% of patients, 7 increasing the RBC ROS production.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…24 We have shown that hypoxia and IS promote eryptosis and alter the RBC redox system, increasing ROS formation and decreasing GSH content. 9 Here, we highlight the role of hypoxia in establishing oxidative stress and show for the first time that uremic serum potentiates these effects. This finding is particularly interesting for HD patients since arterial O 2 saturation can drop below 90% for more than 1/3 of treatment time in about 10% of patients, 7 increasing the RBC ROS production.…”
Section: Discussionmentioning
confidence: 86%
“…Nevertheless, IS reduced GSH in a dose-dependent fashion. 9 We also assessed the activity of important antioxidant enzymes in HD-RBC. SOD plays a critical role in redox homeostasis, converting superoxide into hydrogen peroxide, preventing oxidation of hemoglobin to methemoglobin, which cannot carry oxygen.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, about 10% of patients undergoing HD experience prolonged intradialytic hypoxemia (PIH), a clinical phenotype characterized by an arterial oxygen saturation below 90% for at least one third of the dialysis treatment time (Meyring-Wosten et al, 2016). Previously, we explored the effect of low oxygen partial pressure and the uremic toxin IS on eryptosis (Tozoni et al, 2019). Interestingly, we found that hypoxemia and IS independently increase eryptosis and ROS generation and decrease GSH levels, possibly contributing to the reduced RBC life span observed in CKD (Figures 1, 2).…”
Section: Hypoxia In Dialysis Patients and Its Association With Eryptosismentioning
confidence: 95%
“…Eryptosis can be triggered by a range of both endogenous and exogenous insults, including toxins, drugs, and acute and chronic diseases (Lang and Lang, 2015). Among the uremic solutes that accumulate in CKD, acrolein (Ahmed et al, 2013b), methylglyoxal (Nicolay et al, 2006), and indoxyl sulfate (IS) (Ahmed et al, 2013a;Dias et al, 2018;Tozoni et al, 2019) were shown to increase eryptosis. Moreover, stressors including osmotic shifts, oxidative stress, and energy depletion may also contribute to a shortened RBC survival (Lang et al, 2006).…”
Section: Eryptosis Pathways: Overviewmentioning
confidence: 99%